Nursing care for children with intraosseous access (Research, Society and Development, 2023)
Objective: To evaluate nursing care for children with intraosseous access. Methodology: This is a narrative review of the literature, with a descriptive character and a qualitative approach, carried out from bibliographical surveys of online journals, constituted with the Evidence-Based Practice (EBP) method. The search for articles was carried out in the Latin American and Caribbean Literature in Health Sciences (LILACS), National Library of Medicine (USA) PubMed and SCOPUS databases, as well as in digital collection documents and recent and updated council portals. states, using articles written in Portuguese, English or Spanish with recent publications. Results: 1,365 studies were identified in the search in the databases, after methodological rigor filtering the inclusion and exclusion criteria, a final sample of 10 articles was obtained, being included in this review. Conclusion: In view of the results found in the literature, the technique is widely used in urgencies, emergencies and ICUs in pediatric and adult patients, especially in critical condition with factors that make IV access difficult, being performed by medical professionals and nurses, however there are few studies up to the moment cited with the method being used by nurses, even though they are supported by the Federal Nursing Council - COFEN nº 0648/2020. With this, further studies on the subject are needed, to the point of having greater autonomy for professional nurses related to IO access.